Justification of politics during the Soviet Stalinist era in Kazakhstan from a historical point of view - Haytoğlu, E.; Архыматаева, А.Ж. (BULLETIN of the L.N. Gumilyov Eurasian National University. Historical sciences. Philosophy. Religion Series, 2020)
The main aspects in historical development of the Republic of Kazakhstan were Stalin’s s policy in the 20 – 30s of the twentieth century which was famous as “the Great Repression”. The article was written on the basis of different researches and the historical record. It provides information on eliminating the traditional structure in Kazakhstan by the Soviet government in Stalin’s time, measures to weaken the social and economic forms of the traditional agriculture of the Kazakh people, the country’s industrialization policy, mass collectivization and creation of collective and State farms, the policy on confiscation of the wealthy peasants’ property and challenges related to the population decline. To establish the socialist structure based on the ideology of economy, the political structure and the culture in the Soviet time was carried out with unprecedented extent in the mentality of Kazakh society and consequences of ambiguity which have not occurred in the past .It is significant to realize general trends in the social transformations of the Eurasian multicultural space, the modernization and the culture in order to study this unique experience. The current situation analysis of the scientific knowledge requires understanding Kazakh history from a conceptual viewpoint and clarifying a number of events of selected period. Kazakhstan passed the difficult path in restructuring of a new policy, the economy and the social culture as part of the Soviet Union.